Aktivitas Ekstrak Daun jambu biji (psidium guajava L) sebaai antioksidan menunakan metode DPPH - Ramadani, Sri Ariani (UNIVERSITAS MUSLIM INDONESIA, 2024)
. Literature review Activity on Guava Leaf Extract (Psidium guajava L.) as an antioxidant Using to DPPH Method (Supervised by Faradiba and Aminah). Guava leaf (Psidium guajava L.) is one of the plants having the potential as an antioxidant. Antioxidants can donate their electrons which allow to inhibit, prevent or scavenge the reactions of free radicals and oxidants. The research aimed to determine the highest antioxidant activity on guava leaf extract using different solvents based on the value of IC50 resulted from journal review of antioxidant assay on guava leaf. The research used narrative review methods, inclusion and exclusion literature consisting of national journal/International journal of ISSN standard within the last 10-year published from 2010 to 2020. Guava leaf contains antioxidant activity proven by DPPH method, added with ethanol, and methanol. The keywords used to find the results were antioxidant test, free radicals, DPPH method, guava leaves through Google search and Google Scholar. The results confirmed that guava leaf had antioxidant activity. The strongest antioxidant activity possessed by 70% ethanol extract with IC50 0,2 μg/mL. The value of IC50 lies between <10 μg/ mL categorized as the strongest one.